2011
DOI: 10.1016/j.ssci.2011.01.006
|View full text |Cite
|
Sign up to set email alerts
|

A systemic methodology for risk management in healthcare sector

Abstract: The recent biomedical, technological, and normative changes have led healthcare organizations to the implementation of clinical governance as a way to ensure the best quality of care in an increasingly complex environment. Risk management is one of the most relevant aspects of clinical governance and approaches put forward in literature highlight the necessity to perform comprehensive analyses intended to uncover root causes of adverse events.Contributing to this field, the present paper applies Reason's theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 36 publications
2
89
0
3
Order By: Relevance
“…Efforts specifically focused on standardizing aspects of health care delivery also have been shown to reduce errors (177). In addition, studies have demonstrated potential benefits for patient safety from time management (3), risk management (13), and remediation, i.e., disclosure (40) and apology (60). The literature also highlights common conditions that contribute to the inability of hospitals to reduce errors, such as health care worker stress and burnout (173) and the practice of work-arounds (55).…”
Section: Coordinating At Care Transitions and Across Interdependent Fmentioning
confidence: 99%
“…Efforts specifically focused on standardizing aspects of health care delivery also have been shown to reduce errors (177). In addition, studies have demonstrated potential benefits for patient safety from time management (3), risk management (13), and remediation, i.e., disclosure (40) and apology (60). The literature also highlights common conditions that contribute to the inability of hospitals to reduce errors, such as health care worker stress and burnout (173) and the practice of work-arounds (55).…”
Section: Coordinating At Care Transitions and Across Interdependent Fmentioning
confidence: 99%
“…Lindholm and Host (2009) identified risks using controlled experiments for procurement of medical product. Cagliano et al (2011) used risk breakdown structure to identify risk sources. This paper identifies the risks involved in MPD process through the expertise of development team members.…”
Section: Medical Product Development Phases and Risk Managementmentioning
confidence: 99%
“…A new methodology that combines principles, tools and practices from CRM and HLM could be a solution to facing multiple challenges. As Cagliano et al (2011) claim, the complexity of healthcare requires the adoption of tools coming from different managerial approaches; the development of FMEA and wastes tables suggests the possibility to integrate, at least at tools level, HLM and CRM. Connections between the two approaches have been demonstrated (Cagliano et al, 2011), even if a synergic methodology has been never developed (Crema and Verbano, 2013).…”
Section: Tools and Practicesmentioning
confidence: 99%